Is Capital Structure Study Still A Puzzle? Southeast Asian Panel Data Evidence - Haron, Razali; Ibrahim, Khairunisah; Mat Nor, Fauzias; Ibrahim , Izani (2012)
Issues on inconclusive results in capital structure studies are still unresolved todate. Various perhaps and justifications being put forward by researchers past and present to rationalize their inconsistent findings. Different leverage definitions used in the studies is identified as one of the main factors that lead to inconsistent results recorded in the literature. Different leverage definition serves differently according to the needs of the study thus produces inconclusive findings. Different models employed also play a significant role in this issue of inconsistencies. Different natures of models employed influence greatly the results in capital structure studies throughout. The three countries selected for this study, Malaysia, Thailand and Singapore prove that inconsistent results reported within each country are due to the different definitions of leverage (six leverage measures used) as well as the different models (the static and dynamic models) employed. Inconsistencies are more rampant in the use of different leverage definitions with the same model as compared to different models with the same leverage definition. The Fixed Effect Model and Partial Adjustment Model are employed representing the static and dynamic models respectively. Therefore, the capital structure studies are still craving for one universally accepted leverage definition and also one appropriate model to satisfy the needs of in depth understanding of the relationship between capital structure decisions and value of a firm.